‘I See It, I Want It, I Buy It’: Peran Social Media Marketing dalam Membentuk Brand Image dan Niat Beli Produk Lokal Gen Z: ‘I See It, I Want It, I Buy It’: The Role of Social Media Marketing in Shaping Brand Image and Gen Z’s Intention to Purchase Local Product - Evi C Waworuntu; Deske W Mandagi; Anthony S Pangemanan (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2022)
Although the interplay of social media marketing (SMM) on brand image and purchase intention has been studied extensively, insights into the link between these variables in the context of the local product remain scarce, specifically from generation Z’s customer point of view. Therefore, this study aims to fill this theoretical gap by investigating the role of SMM on brand image and purchase intention of local products in the perception of generation Z. A survey-based data was collected using purposive sampling from 184 respondents of generation Z. The data were then analyzed using SmartPLS statistical software. The result reveals that SMM positively and significantly influences the brand image and Gen Z’s intention to purchase the local product. Meanwhile, brand image was a positive predictor of purchase intention. Additionally, brand image mediates the relationship between SMM and purchase intention, such that SMM influences brand image, leading to purchase intention.